2011 9th IEEE Symposium on Embedded Systems for Real-Time Multimedia 2011
DOI: 10.1109/estimedia.2011.6088516
|View full text |Cite
|
Sign up to set email alerts
|

Automatic derivation of polyhedral process networks from while-loop affine programs

Abstract: The Process Networks (PNs) is a suitable parallel model of computation (MoC) used to specify embedded streaming applications in a parallel form facilitating the efficient mapping onto embedded parallel execution platforms. Unfortunately, specifying an application using a parallel MoC is very difficult and highly error-prone task. To overcome the associated difficulties, an automated procedure exists for derivation of a specific polyhedral process networks (PPN) from static affine nested loop programs (SANLPs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As can be seen in the template from Figure 10a the acqProd statement is fired η(ti, bx) number of times in the initial segment. This can also be seen in (15). After stuffing zeros to complete the initial segment, the remainder of the array is acquired, followed by stuffing zeros to fill the phase list.…”
Section: Empty Space Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in the template from Figure 10a the acqProd statement is fired η(ti, bx) number of times in the initial segment. This can also be seen in (15). After stuffing zeros to complete the initial segment, the remainder of the array is acquired, followed by stuffing zeros to fill the phase list.…”
Section: Empty Space Consumptionmentioning
confidence: 99%
“…Polyhedral analysis techniques are often used for analyzing and reordering communication patterns in multi-core systems [2,15]. The polyhedral model is a compact representation of the PDG.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The pn-tools presented in [15] automatically parallelizes sequential applications. A polyhedral model is used to analyze the application behavior and to generate the parallel implementation.…”
Section: Related Workmentioning
confidence: 99%
“…In [1] it is shown that the temporal behavior of an application generated by the pn-tools can be analyzed with a Cyclo-Static Dataflow (CSDF) model. Support for the parallelization of while-loops is added in [15], but without the generation of a temporal analysis model.…”
Section: Related Workmentioning
confidence: 99%